Advances in computational intelligence, security and Internet of Things : second International Conference, ICCISIoT 2019, Agartala, India, December 13-14, 2019, proceedings /: second International Conference, ICCISIoT 2019, Agartala, India, December 13-14, 2019, proceedings. (2020) - Unknown
No abstract available